2016
DOI: 10.1053/j.gastro.2016.06.043
|View full text |Cite
|
Sign up to set email alerts
|

ADAR-Mediated RNA Editing Predicts Progression and Prognosis of Gastric Cancer

Abstract: Our study highlights a major role for RNA editing in GC disease and progression, an observation potentially missed by previous next-generation sequencing analyses of GC focused on DNA alterations alone. Our findings also suggest new GC therapeutic opportunities through ADAR1 enzymatic inhibition or the potential restoration of ADAR2 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 59 publications
7
126
1
Order By: Relevance
“…Although RNA editing was initially considered to be a rare event, limited specifically to coding exons within genes, high-throughput sequencing data have now revealed that it occurs more prevalently (23). In particular, A-to-I RNA editing mediated by ADARs is the most prominent form of RNA editing in humans, and various studies have recently demonstrated cancer-specific dysregulation of ADAR as well as subsequent site-specific RNA editing in several human cancers (9)(10)(11)24). More specifically, AZIN1 has been identified as one of the most frequently edited genes in HCC and esophageal cancers (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Although RNA editing was initially considered to be a rare event, limited specifically to coding exons within genes, high-throughput sequencing data have now revealed that it occurs more prevalently (23). In particular, A-to-I RNA editing mediated by ADARs is the most prominent form of RNA editing in humans, and various studies have recently demonstrated cancer-specific dysregulation of ADAR as well as subsequent site-specific RNA editing in several human cancers (9)(10)(11)24). More specifically, AZIN1 has been identified as one of the most frequently edited genes in HCC and esophageal cancers (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…AZIN1 ( 9 , 44 ) and NEIL1 ( 62 ) ) and impairs editing frequencies of ADAR2 substrates (e.g. COPA ( 46 ), GluA2 ( 63 ) and PODXL ( 32 ) ), respectively, are involved in cancer development and progression. As a bidirectional regulator of A-to-I editing, DHX9 reshapes the editing profiles, which may further contribute to the dysregulation in editing and confer malignant transformation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A bioinformatics pipeline adapted from a previously published method (31) was used to identify RNA editing events (32). For each sample, raw reads were mapped to the reference human genome (hg19) and a splicing junction database generated from transcript annotations derived from UCSC, RefSeq, Ensembl and GENCODE (v19) by using Burrows–Wheeler Aligner with default parameters (bwa mem algorithm, v0.7.15-r1140) (33).…”
Section: Methodsmentioning
confidence: 99%
“…In gastric cancer, high ADAR1 levels are correlated with increased cell proliferation and metastasis. While one group reported earlier that the higher expression of ADAR1, together with lower ADAR2 levels, led to a “misedited” phenotype [142], another group suggested that ADAR1p150′s function was to promote the mTOR signaling pathway by phosphorylation [143], although whether editing also occurred was unclear. Further studies would be needed to determine how ADAR1p150 regulates phosphorylation of proteins like mTOR, and whether this pathway is generalizable to other cancers that are also associated with imbalances in ADAR1 levels.…”
Section: Regulation Of Adar1 Expressionmentioning
confidence: 99%